Metode Speed Play terhadap kapasitas kardiorespirasi atlet - Irvan Irvan; Arifuddin Usman; Arimbi Arimbi (Seminar Nasional LP2M UNM, 2019)
This study  to determine how the effects of routine training with the speed play method in increasing the cardiorespiratory capacity of athletes. This study is a pre-experimental study or pre-experimental design which is a study that is used to find a causal relationship where randomization is not done and does not use a control group. The research design uses The one-group Pre-posttest Design. In this study a group of subjects or experimental units were selected. The instrument used in this study was Multistage Test (MFT) for cardiorespiration. The results of this study showed that after giving a speed play training method, the average cardiorespiratory capacity after giving an athlete's speed play training method was 43.49 ml / kg / minute higher than the average cardiorespiratory capacity before giving a speed play training method to the basketball team phinisi 40.95 ml / kg / minute there is an average increase of 2.54 ml / kg / minute.